Consumers' food choices, understanding and perceptions in response to different front-of-pack nutrition labelling systems in Belgium: results from an online experimental study - Stefanie Vandevijvere; Marie Vermote; Manon Egnell; Pilar Galan; Zenobia Talati; Simone Pettigrew; Serge Hercberg; Chantal Julia (BMC, 2020)
Abstract Background Front-of-pack nutrition labels (FoPLs) are increasingly implemented by governments internationally to support consumers to make healthier food choices. Although the Nutri-Score FOPL has officially been implemented in Belgium since April 2019, no study has been conducted before its implementation to compare the effectiveness of different FOPLs. Methods The aim of this study was to compare food choices, objective understanding and perceptions of Belgian consumers in response to five different FOPLs, currently implemented in different countries internationally, namely the Health Star Ratings (HSR), the Multiple Traffic Lights (MTL), Nutri-Score, Guideline Daily Amounts (GDA), and Warning symbols. During the summer 2019, 1007 Belgian consumers were recruited and randomized to one of the five different FOPLs. Through an online questionnaire they were asked to choose one of three different foods within each of three categories (pizzas, cakes, breakfast cereals), as well as rank those same three foods according to nutritional quality, in the condition without as well as with FOPL. In addition, various questions were asked on their perceptions in relation to the FOPL they were exposed to. Results Perceptions of consumers were favorable for all FOPLs with no significant differences between the different FOPLs. There were no significant differences in food choices among the different FOPLs, but Nutri-Score performed best for ranking food products according to nutritional quality. Conclusions While there were no significant differences among different FOPLs for food choices and perceptions, the Nutri-Score was the most effective FOPL in informing Belgian consumers of the nutritional quality of food products.